La presencia de la madre muerta en el drama romántico español - Prado Mas, María (Dicenda. Estudios de lengua y literatura españolas, 2003)
The objective of this work is to analyze the appearance of the figure of the dead mother in the Spanish Romantic Drama as a symbol of forsakenness and helplessness of mankind. Evoked by male and female characters in the most intense moments of the action, her presence, protective and beloved, reflects the Romantic perception of mankind in the world: a human being left into a place hostile to all hope.